Sports and nationalism in Latin/o America - Fernández L'Hoeste, Héctor D. 1962-; Irwin, Robert McKee 1962-; Poblete, Juan 1962- (Palgrave Macmillan, 2015)
"This book presents a broad selection of research on connections between sports and nationalism in Latin American and the Latino USA. It brings a critical cultural studies approach to studies of both historical and contemporary contexts from throughout the Americas, with a focus on the region's emblematic sport of soccer, as well as baseball, boxing, paralympic sports, surfing, tennis and basketball, among others"--
Literaturangaben
Keywords: Sports / Latin America / History; Nationalism and sports / Latin America / History; Sports / Social aspects / Latin America; SOCIAL SCIENCE / Ethnic Studies / Hispanic American Studies; SOCIAL SCIENCE / Media Studies; SPORTS & RECREATION / General; Nationalism and sports; Sports; Sports / Social aspects; Geschichte; Gesellschaft; Hispanos; Sport; Nationalismus; Latin America; Lateinamerika; USA; Aufsatzsammlung